Effects of different sport surfaces on muscle performance - Katkat, D.; Bulut, Y.; Demir, M.; Akar, S. (Biology of Sport, 2009)
The aim of the present study was to examine the effects of different sport surfaces on athletic performance by means of muscle performance. Twenty two elite male basketball players, aged between 17 and 28, participated in this study. This study was executed on 7 different sport surfaces: asphalt, synthetic grass, natural grass, tile powder, soil, wooden parquet and EPDM (Ethylene Propylene Diene Monomer). Leg strength (LS) and vertical jumping height (VJH) were measured at rest and after a given training protocol on each surface. Surface compliance was evaluated with a drop test using a medicine ball. Asphalt and synthetic grass were the most fatiguing, natural grass, soil and tile powder were moderately fatiguing, parquet and EPDM were the least fatiguing surfaces. The results of surface compliance were inconsistent with those obtained in LS and VJH tests. As the compliance of the surface increased LS and VJH increased, i.e. performance was decreased. The results of the present study suggest that it is better to use parquet and EPDM in construction of indoor sport surfaces. On the other hand, it may be appropriate to build outdoor surfaces with natural grass because of its aesthetic and visual impacts and its contribution to the amount of urban green area.